Model Sinergisitas Badilag dan DSN-MUI Dalam Menguatkan Sistem Ekonomi Syariah di Indonesia - Mashudi Daud (Journal of Economics and Development, 2024)
The Constitutional Court issued decision Number 93/PUU-X/2012 which strengthened the position of the Religious Courts as the authority to resolve sharia banking disputes through litigation. However, sharia economic cases, especially sharia banking disputes that go to the Religious Courts and Syar'iyah Courts, are considered not optimal in almost all of Indonesia. One of the problems that is being highlighted is the minimal number of Religious Court Judges who have been certified in Sharia Economics, because in terms of ratio only 30% of the quota of judges certified in Sharia Economics is the ideal number in all of Indonesia. This research tries to explore this problem by analyzing it from upstream to downstream problems by offering the concept of Synergy between Badilag and DSN-MUI in Strengthening Sharia Economic Law in Indonesia. The method used in this research is a literature study using qualitative descriptive. There are several things that can be more optimally synergized between the Director General of Badilag and DSN-MUI, including Strengthening Competencies in the Sharia Economics Field through Accelerating Judge Training in Each Religious High Court and Unification of Product Contracts through Cross-Cooperation between Badilag, DSN-MUI and Banks Sharia throughout Indonesia.